Effect of insect farming by-product (frass) as a novel bedding material on litter quality, growth performance, carcass traits, and meat quality of broiler chickens - Tóth, Márk; Birolo, Marco; Palumbo, Bianca; Nalon, Eleonora; Frangipane di Regalbono, Antonio; Giaccone, Valerio; Erdélyi, Márta; Dalle Zotte, Antonella (Frontiers in Animal Science, 2026)
IntroductionThe use of insect-derived by-products as litter amendments may represent a sustainable strategy in broiler production. The present study evaluated the effects of supplementing wood shavings with different inclusion levels of yellow mealworm (Tenebrio molitor) frass on litter quality, growth performance, slaughter traits, and the meat quality of broiler chickens.MethodsA total of 352 one-day old Ross 308 male broilers were allocated to 16 pens (4 replicates per treatment; 22 chicks per replicate) with four bedding treatments: 100% wood shavings (FO, control), or wood shavings supplemented with 10% (F10), 20% (F20), or 30% (F30) of frass. Individual live weight (LW) and daily weight gain (DWG), and pen-level daily feed intake (DFI) and feed conversion ratio (FCR) were recorded during the trial. At 42 days of age, chickens were slaughtered to assess carcass yield, cut proportions, and the occurrence of breast myopathies, while meat quality parameters were measured on breast (pectoralis major) and thigh (iliotibialis lateralis) muscles.Results and DiscussionThe DFI was significantly reduced at all frass inclusion levels compared to the control group. Final LW (P = 0.012), and overall DWG (P = 0.004) were significantly lower in F10 and F30 compared with FO, while overall FCR was not affected. Carcass and breast yields did not differ among treatments, while thigh yield was significantly reduced in FO group (P = 0.023). Breast myopathies and meat quality parameters remained unaffected by the bedding treatments. These findings indicate that yellow mealworm frass can be supplemented in conventional bedding materials in broiler production without compromising meat quality traits. However, in F30 group growth performance and breast yield were impaired, suggesting that frass inclusion should not exceed 20%.